Metal injection moulding of hip stem CoCrMo alloy powder using palm stearin binder system - Omar, Mohd Afian; Abdullah, Noorsyakirah; Sauti, Rosliza; Mohd Zainon, Nurazilah; Johari, Nurhaslina; Zulkifly, Ahmad Hafiz; Baharuddin, Mohd Yusof (Trans Tech Publications Ltd., Switzerland, 2016)
Metal Injection Moulding (MIM) has undergone development of various binder systems with the aims of shortening the overall debinding time duration. In the present work, binder system based on biopolymer has been utilised in injection moulding of hip stem CoCrMo alloy powder. The feedstock consisted of CoCrMo powder with mean diameter particle size of 16 μm and binder which comprised of major fraction of wax and minor fraction of polyethylene. The moulded part was immersed into n-heptane at 60 °C in order to remove the palm stearin, followed by sintering in a controlled vacuum atmosphere. Results showed that solvent extraction debinding technique allowed complete removal of palm stearin from the injection moulded part within 5 hours without swelling or distortion of the debound part. Lower heating rate is needed during thermal pyrolysis in order to retain the shape due to the thickness of the part.